2021
DOI: 10.14297/jpaap.v9i2.483
|View full text |Cite
|
Sign up to set email alerts
|

Early adopters versus the majority: Characteristics and implications for academic development and institutional change

Abstract: The diffusion of innovation curve has become common parlance when considering the adoption of technology-enhanced learning in higher education. Innovators, early adopters, early majority, late majority and laggards indicate the different rates of technology adoption. This study explored the views and experiences of staff at one research-led institution within one of four colleges, to determine whether there were differences between the characteristics and digital academic practices of teachers, based on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Secondly, Uganda is often considered a model of DSD delivery and uptake and countries such as Ghana have undertaken visits to the country to learn from its DSD implementation experience [ 30 , 31 ]. The HIV Policy Lab data of 2022 reveals that Uganda is one of the countries which has adopted all three salient features of differentiated HIV treatment services which include community ART distribution, maximum flexibility for clinic visits and multi-month dispensing [ 18 ]. Select providers in Uganda piloted select DSD models (such as FTDR) prior to their formal endorsement by the WHO in 2016 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, Uganda is often considered a model of DSD delivery and uptake and countries such as Ghana have undertaken visits to the country to learn from its DSD implementation experience [ 30 , 31 ]. The HIV Policy Lab data of 2022 reveals that Uganda is one of the countries which has adopted all three salient features of differentiated HIV treatment services which include community ART distribution, maximum flexibility for clinic visits and multi-month dispensing [ 18 ]. Select providers in Uganda piloted select DSD models (such as FTDR) prior to their formal endorsement by the WHO in 2016 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…We utilize an implementation research lens [ 17 ] to understand drivers of ‘early adoption’ [ 18 ] of differentiated HIV treatment services, with Uganda as a country case study. The implementation science literature distinguishes between ‘early adopters’ and ‘late adopters’ of health care innovations [ 18 ]. Rogers (2003) introduced the notion of five categories of adopters (Innovators, Early Adopters, Early Majority, Late Majority, and Laggards) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology adoption (or diffusion) is the process by which the market for a new technology transform over time (Stoneman and Battisti, 2010). Previous research has suggested the existence of five types of adopters, including innovators, early adopters, early majority, late majority and laggards (Dale et al, 2021). Rogers defined diffusion as a "special form of communication" (1995, p. 5) where new ideas are spread from individual to individual over time (Rogers, 2003;Straub, 2009), indicating the critical importance of communication during the technology adoption process between the various types of technology adopters.…”
Section: Introductionmentioning
confidence: 99%